On rural teaching in the districts of Strandasýsla and Húnavatnssýsla 1887– 1905 - Guðmundsson, Bragi (Menntavísindasvið Háskóla Íslands, 2021)
From shortly before the middle of the 18th century, Icelandic homes were obliged to provide children with instruction in religion and reading. This obligation was extended in 1880, when writing and arithmetic were added. The homes were supposed to provide the instruction, monitored by parish priests. By the middle of the 19th century, the need for schools for children and teenagers was generally recognized and they were founded one by one, primarily in urban areas. In the countryside, teaching mainly took place in homes and clergymen were supposed to monitor the children’s progress.Many were concerned about the lack of schools but proponents of improved education often had to tackle obstacles deeply rooted in Icelandic history and culture, as well as in the firm belief that home schooling was a cornerstone of society. There were also economic hindrances due to the high level of poverty amongst the general population and an ingrained reluctance to use public funds to cover communal expenses.This article is based on data regarding rural teaching in two districts in the Húnaflói Bay area; that is, Strandasýsla and Húnavatnssýsla, prior to the formal introduction of compulsory education in 1907. The National Archives of Iceland hold reports from 1887 and onwards that deal with grant applications from rural teachers. The aim is to shed some light on the students who received this teaching and their circumstances.The main conclusions are the following:The age distribution of children and teenagers in the Húnaflói Bay area around the turn of the 20th century was more or less the same as elsewhere in the country. The proportion of children who were taught by rural teachers gradually grew; nevertheless the two districts were well below the national average as regards the proportional school attendance of Icelandic youth.There was a clear difference between the municipalities in Strandasýsla as regards the level of children’s formal education. It was lowest north of Steingrímsfjörður but increased in the southern parts. ...